Enhancing institutional capacity in a centralized state: The case of industrial water use efficiency in Vietnam. (22nd December 2022) - Trang, Tran Thu; Bush, Simon R.; van Leeuwen, Judith
Abstract: This article uses an institutional capacity framework to assess the interplay between the macro level institutional environment in the form of the centralized Vietnamese state, and the meso level institutional capacity of three different industrial zones to develop technological water use efficiency strategies. Our results show that the relational, knowledge, and mobilization capacities of these industrial zones are constrained by the centralized nature of the Vietnamese state. These industrial zones also show a limited capacity to instigate reform of macro level regulatory institutions. However, we also find instances where industrial zones do demonstrate capacity for implementing water use efficiency technologies because of their capacity to coordinate relations with client firms, universities, and provincial industrial zone authorities. If the institutional capacities of industrial zones are better supported, we argue there remains room for them to influence the macro institutional context to support innovation in water use efficiency. Our results indicate the value of institutional capacity as a framework for assessing processes of technical innovation for industrial ecology, especially in the context of centralized states.